Construction of pH‐responsive core crosslinked micelles via thiol‐yne click reaction. Issue 32 (22nd June 2022) - Niu, Yile; Lu, Yanbing
Abstract: Polycarbonate‐based micelles possessed enormous potential for hydrophobic drug delivery. To improve micelle stability and prevent premature leakage during blood circulation, photo‐induced thiol‐yne click reaction was utilized to construct polycarbonate‐based core crosslinked micelles (CCLMs), which avoided the use of toxic copper catalyst. The introduced β‐thiopropionate linkage in the core was demonstrated to endow the CCLMs with pH‐responsiveness. The obtained CCLMs showed good dilution stability against DMF and water. Further MTT assays demonstrated excellent biocompatibility and low toxicity of the CCLMs in HeLa/MCF‐7 cells. Moreover, DOX‐encapsulated CCLMs showed good anticancer effects and excellent internalization efficiency in HeLa cells. The pH‐responsive polycarbonate‐based CCLMs by thiol‐yne click reaction have potential used as smart delivery systems for controlled drug release. Abstract :